2020
DOI: 10.1371/journal.pone.0241957
|View full text |Cite
|
Sign up to set email alerts
|

Twitter reveals human mobility dynamics during the COVID-19 pandemic

Abstract: The current COVID-19 pandemic raises concerns worldwide, leading to serious health, economic, and social challenges. The rapid spread of the virus at a global scale highlights the need for a more harmonized, less privacy-concerning, easily accessible approach to monitoring the human mobility that has proven to be associated with viral transmission. In this study, we analyzed over 580 million tweets worldwide to see how global collaborative efforts in reducing human mobility are reflected from the user-generate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
146
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 204 publications
(157 citation statements)
references
References 50 publications
5
146
0
6
Order By: Relevance
“…A study of 580 million tweets posted during the early months (ie, January to May 2020) of the pandemic showed that the geographic information associated with tweets can be used as a proxy for human mobility. 4 Public health organizations can use this realtime data to inform messaging content and where to target hyperlocal messages about public health measures (eg, shelter in place).…”
Section: Surveillance Of Digital Data To Inform Public Health Messagingmentioning
confidence: 99%
“…A study of 580 million tweets posted during the early months (ie, January to May 2020) of the pandemic showed that the geographic information associated with tweets can be used as a proxy for human mobility. 4 Public health organizations can use this realtime data to inform messaging content and where to target hyperlocal messages about public health measures (eg, shelter in place).…”
Section: Surveillance Of Digital Data To Inform Public Health Messagingmentioning
confidence: 99%
“…Population mobility was assessed using the number of people (Twitter users) with moving distance larger than 0.5 mile per day in SC and the selected counties. The methodology of extracting daily population movement (origin-destination flows) from geotagged tweets is discussed elsewhere [18,19]. Briefly, geotagged tweets during the study periods were collected and used for calculation.…”
Section: Methodsmentioning
confidence: 99%
“…Daily travel distance was calculated for each user based on the derived origin-destination flows and used to generate a variable of how many people moved each day (with travel distance larger than 0.5 mile). This method of capturing population mobility through Twitter has been previously validated [18].…”
Section: Methodsmentioning
confidence: 99%
“…Third, a more recent data source is the data retrieved from the increasingly popular social media applications (e.g., Facebook and Twitter). Such social media data contain spatial and temporal information obtained from users when they choose to post contents with locations, generating diverse index-based mobility data at the aggregated levels, such as the mobilitybased responsive index (Huang et al, 2020;Jurdak et al, 2015). Future studies need to put efforts to compare the quality of these multi-source mobility data and explore the possible replacement of data to improve data availability to public and researchers.…”
Section: The Involvement Of Multi-source Mobility Datamentioning
confidence: 99%